Revisiting the role of the attorney general as the protector of public charitable trust in Malaysia in comparison with the position in England and Wales - Ali, Zuraidah (2015)

(untitled)
ABSTRACT The concept of Public Trust of better known as charitable trust bears no difference with the ones administered under the English Law. Since English law bears no strict legal definition of charity, all concept of charity and purposes has its origin from the Preamble to Charitable Uses Act 1601. Despite the non-exhaustive list of charitable purposes, the charitable purposes can basically be classified to four, namely the relief of poverty, secondly, the advancement of education; thirdly the advancement of religion and lastly other purposes beneficial to the community. Charities are exempted from taxes and it also have to preserve the element of public benefit. There is a need for charities to be well protected. Unlike in England and Wales, where the existence of the Charity Commission marks the continuous protection of any charitable trust or organization, the concept of Attorney General as the protector of charitable trust must be looked as very vital due to non-existence of the Charity Commission in Malaysia. The power given to Attorney General can be found under section 9 of the Government Proceeding Act 1956 and the official role of the Attorney General is to initiate a suit on behalf of the charity. This paper will revisit and examine the current role that the Attorney General plays as the protector of this trust in Malaysia in comparison with the position of the Attorney General in England and Wales.